1997
DOI: 10.1101/gad.11.3.334
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the ASF/SF2 RS domain affects both protein-protein and protein-RNA interactions and is necessary for splicing.

Abstract: ASF/SF2 is a member of a conserved family of splicing factors known as SR proteins. These proteins, which are necessary for splicing in vitro, contain one or two amino-terminal RNP-type RNA-binding domains and an extensively phosphorylated carboxy-terminal region enriched in repeating Arg-Ser dipeptides (RS domains). Previous studies have suggested that RS domains participate in protein-protein interactions with other RS domain-containing proteins. Here we provide evidence that the RS domain of unphosphorylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
357
0
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(369 citation statements)
references
References 59 publications
(75 reference statements)
8
357
0
4
Order By: Relevance
“…For example, the phosphorylation status of splicing factor 2\alternative splicing factor (SF2\ASF) differentially affects its associations with several SR-related proteins in itro [38]. Phosphorylation of SF2\ASF protein enhances its interaction with U1 snRNP-specific 70 kD protein in itro [39], perhaps by strengthening the ionic interaction of RS domains through constituting a ' polar zipper ' [40]. On the other hand, SF2\ASF phosphorylation decreases its binding to SRp40 and has no obvious influence on its association with U2AF35 [38].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the phosphorylation status of splicing factor 2\alternative splicing factor (SF2\ASF) differentially affects its associations with several SR-related proteins in itro [38]. Phosphorylation of SF2\ASF protein enhances its interaction with U1 snRNP-specific 70 kD protein in itro [39], perhaps by strengthening the ionic interaction of RS domains through constituting a ' polar zipper ' [40]. On the other hand, SF2\ASF phosphorylation decreases its binding to SRp40 and has no obvious influence on its association with U2AF35 [38].…”
Section: Discussionmentioning
confidence: 99%
“…The RBD consists of RNP-2 and the highly conserved RNP-1, which contains the signature sequence RDAEDA and is important for RNA interaction in a substrate-dependent manner (Reed 1996). SR domains can participate in speci®c protein±protein interactions (Kohtz et al 1994;Xiao & Manley 1997), are generally phosphorylated in vivo (Gui et al 1994;Colwill et al 1996) and play important roles in nuclear localization . Both the NSSR 1 and 2 proteins show conservation of these important domains.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, if the cis-acting element is positioned within the intron, interaction with SR proteins can actually lead to the opposite effect, that is, splicing repression (Kanopka et al 1996). Finally, the RS domain of SR proteins is highly phosphorylated (Roth et al 1990), with the level of serine phosphorylation able to alter SR protein activity (Cao et al 1997;Xiao and Manley 1997;Kanopka et al 1998). This last feature allows for the modulation of SR protein activity in either constitutive or alternative splicing events.…”
mentioning
confidence: 99%
“…Specific phosphatases including protein phosphatase 1 (PP1) have been shown to affect in vitro splicing (Mermoud et al 1992(Mermoud et al , 1994aCardinali et al 1994;Cao et al 1997). In addition, thiophosphorylation of splicing factors interferes with pre-mRNA splicing (Tazi et al 1992(Tazi et al , 1993Xiao and Manley 1998). More directed experiments have demonstrated that the state of phosphorylation of SR proteins in particular can be linked to splicing activity in vitro.…”
mentioning
confidence: 99%